A Study of Students’ Reading Skill in Comprehending Genre of the Text at STIE-SAK Academic Year 2025/2026 - Yelnim Yelnim; Suci Marselina; Sukarta Kartawijaya (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This research was descriptive research, the aim of the research was to analyze students’ skill in comprehending genre at second semester of economic development major at STIE-SAK academic year 2025/2026. The population of this research was students at second semester of economic development major at STIE-SAK. There was a class which consisted of number of population was 21 students. Then, the sample of the research was taken by using total sampling technique. In this case, all of the students in the class would become the sample. The data of this study were students’ skill in comprehending genre of descriptive text. It was focused in generic structure and specific information. The data was collected by using reading test. Before the writer gave reading test to the sample, the test was tried out. To know the validity and reliability of the test, the writer used Pearson Product Moment and Spearman-Brown formula. It was found that the reliability of the test was high correlation (0.61). The result of the data showed that the students’ reading skill in comprehending the descriptive text was low. It could be seen from the data, the majority of the students who got high score was 4.76 %, and the total of low score was 33.33 %. Connected to the result, the writer suggests the students to practice their reading skill specially in genre of descriptive text. If they practice more, they will have good reading ability. To the English leturer, the writer suggests to give more explanation and exercises for students related with genre of descriptive text. Then for the other researcher, the writer suggests to study the students’ difficulties in genre of descriptive text.